Caracterização da qualidade da água na Barragem do Perímetro Irrigado de Jacarecica I, Itabaiana, Sergipe. - Silva, Marinoé Gonzaga da (2006)
Water resources preservation is a worldwide issue, mainly regarding to the availability to several human uses, including irrigated agriculture. The increasing concern about water quality and quantity is stimulating studies on dynamics of reservoirs and other water bodies. The acquired knowledge is of crucial importance for better management of a watershed and its components, especially when irrigated agroecosystems are present. The objective of this study was to characterize the quality of the water used in the Jacarecica I Irrigation District, situated in the Jacarecica River watershed, Sergipe, Brazil. The water quality was characterized using physicochemical and biological parameters obtained from water samples collected in January, March, May, July, and October of 2005. The field and laboratory measurements were pH, transparency, temperature, electrical conductivity, ammonia, nitrite, nitrate, total nitrogen, total phosphorus, dissolved oxygen, chlorophyll a, turbidity, sodium, potassium, calcium, magnesium, boron, chloride, bicarbonate, sulfate, fecal and total coliform. It was confirmed the utility of these parameters as water quality indicators for environmental monitoring purposes and for verification of the reservoir water adaptability to human and irrigation uses. The reservoir water ranged from eutrophic to oligotrophic depending on the season of the year and the sampling location, occurring reduction of the trophic state from the river to the dam. The limiting nutrient in the reservoir was the nitrogen during the dry season and the phosphorus during the rainy season. The reservoir water hydrochemistry was homogeneous with predominance of chloride sodic water. According to USDA classification, the reservoir water is C2-S1, in both dry and rainy seasons. Considering FAO’s guidelines, there were restrictions to water use due to sodium in the dry season and bicarbonate in both dry and the rainy seasons.